From the Pole to the Equator: Encounters with the Nonhuman in Nineteenth-Century Italian Narratives of Polar Exploration - Lolla, Maria Grazia (Quaderni d'Italianistica, 2023)
This paper examines depictions of wildlife in accounts of Italian polar exploration—both factual and fictive—at the turn of the 20th century, applying a posthumanist ecocritical perspective to a cultural imaginary encompassing Emilio Salgari’s adventure writings as well as colonial exploration’s science and practice. It begins with two sources revealing an era of exploration marked by implicit animal violence: avant-garde filmmakers Yervant Gianikian and Angela Ricci Lucchi’s Dal polo all’equatore (1986), a reframed version of colonial footage by Luca Comerio, and the chronicle of the Italian North Pole expedition led by the Duke of Abruzzi (1899–1901). Comparative analysis then turns to Salgari’s polar fiction, re-evaluated here as an aspirational vision privileging wildlife observation. I argue for a recalibration of human-animal interactions, highlighting how figurations of accounts of human animal cruelty and animal awareness interweave with the actions of explorers who alternately harmed or protected wildlife.